Development of Village Information System using Waterfall and TAM Method in XYZ Ward - Suwarno Suwarno; Yefta Christian; Jonathan Jonathan; Marvin Christian; Vendryan Vendryan; Chris Tan (JURIKOM (Jurnal Riset Komputer), 2023)
The digital village initiative that is supported by the Indonesian Government is closely related to the development and utilization of digital infrastructure to improve people's welfare. In this study, we present the development and implementation of a village information system to support digital village initiatives in XYZ Ward, Batam. These systems include a civil registration system and a public complaint reporting system aimed to improve service delivery and communication between the government and the public. The Software Development Life Cycle (SDLC) method, specifically waterfall method, was used to develop the system, and using the Technology Acceptance Model (TAM) to evaluate people's acceptance towards the system. The evaluation yielded promising results with a score of 85% strongly agreeing with the usefulness of the systems, 88% strongly agreeing with the systems’ ease of use, and 86% accepting the use of the systems overall in their daily lives. The study concludes that digital village community systems can contribute to improving government services and suggest future research to support similar initiatives in other areas